Dexamethasone-loaded carboxymethylchitosan/poly(amidoamine) dendrimer nanoparticles enhances bone formation in vivo - Oliveira, J. M. (2008)
[Excerpt] Dexamethasone-loaded carboxymethylchitosan/poly(amidoamine) dendrimer nanoparticles, CMC/PAMAM-Dex were successfully synthesized to ﬁnd applications as a controlled system of relevant molecules in Bone Tissue Engineering. These are aimed at modulatingtheproliferation anddifferentiationofstem cells,both invitro and in vivo. In previous work, we have demonstrated that CMC/ PAMAM-Dex nanoparticles are internalized with high efﬁciency by different cell types, namely osteoblastic-cells, SaOs-2 and rat bone marrow stromal cells, RBMSCs. The biocompatibility of HA and SPCL scaffolds was also assessed by means of seeding RBMSCs onto the materials and performing a luminescent cell viability assay, after 24 and 72hrs. [...]